Criminal Acts of Corruption Procurement of Goods and Services of Local Governments through Electronic Procurement Services (LPSE) - Yasmirah Yasmirah; Firman Halawa; Sukur Tandiono; T. Riza Zarzani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The rapid advancement of technology is seen as one of the right and effective methods to increase the transparency of public information access, by implementing an online system for goods/services procurement or known as Electronic Procurement Services (LPSE).  But corruption in the goods/services procurement of the local government continues even though the LPSE has been implemented. The purpose of this research is to knowing legal arrangements, forms of irregularities, and to explain the efforts of Government Internal Supervisory Apparatus (APIP) in preventing corruption in the goods and services procurement of the local government carried out through LPSE The research method used is a qualitative method that is descriptive. The type of juridical research is normative, that is literature study with secondary data types consisting of primary, secondary, tertiary legal materials. The legal arrangements related to the corruption of the public goods/services procurement are regulated in Law No. 31 of 1999 Jo. Law No. 20 of 2001, while the legal arrangements for the public goods/services procurement through LPSE are regulated in Presidential Regulation No. 16 of 2018 Jo. No. 12 of 2021 concerning the Public Procurement Goods/Services. LKPP Regulation as technical guidelines are LKPP Regulation No. 9 of 2018, No. 11 of 2018 Jo. No. 7 of 2020, and No. 14 of 2018. The configuration of irregularities that occur in the public goods/services procurement through LPSE include corruption regulated in Corruption Law, as well as irregularities in the form of administrative irregularities and general crimes, unfair business competition law, and corruption. The efforts of APIP in preventing corruption in the public goods/services procurement is an early warning at every phase of the goods/services procurement and the efforts of LKPP strengthening the Electronic Procurement System (SPSE) by using online-based applications, and law enforcement by firm and fair criminal sanctions to the corruptor in the goods/services procurement in accordance with the applicable corruption law.